PERANCANGAN SISTEM INFORMASI TRANSAKSI HARIAN PERPAJAKAN ATAS JASA DI DINAS BINA MARGA DAN PENATAAN RUANG PROVINSI JAWA BARAT - Adian Nugroho Samosir; Hani Kustyanti Kusnadi; Candra Mecca Sufyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The tax information system is an effort to improve tax services, by making changes to the use of information technology and information systems, one of which is Income Tax. In carrying out its activities, Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat found a process for recording tax transaction data still using an input process with Microsoft Excel. The author has found the best solution for processing daily transaction lists at the Highways and Spatial Planning Office, the solution is in the form of a web with the PHP programming language and MySQL database called E-Bimatax